Unsteady micropolar fluid over a permeable curve stretching shrinking surface - Saleh, Siti Hidayah Muhad; Arifin, Norihan Md.; Nazar, Roslinda; Pop, Ioan (Hindawi Publishing Corporation, 2017)
This work deals with the unsteady micropolar fluid over a permeable curved stretching and shrinking surface. Using similarity transformations, the governing boundary layer equations are transformed into the nonlinear ordinary (similarity) differential equations. The transformed equations are then solved numerically using the shooting method. The effects of the governing parameters on the skin friction and couple stress are illustrated graphically. The results reveal that dual solutions exist for stretching/shrinking surface as well as weak/strong concentration. A comparison with known results from the open literature has been done and it is shown to be in excellent agreement.